PENGARUH PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN BANK SULTRA CABANG PEMBANTU KONAWE KEPULAUAN - Sahyunu, Sahyunu; Utha, Rasidin; Savitri, Evin (Sultra Journal of Economic and Business, 2022)
This research was conducted at the Konawe Islands Sub-Branch of Southeast Sulawesi Bank. This research is whether the financial performance of the Konawe Islands Sub-Branch Sultra Bank using the CAMEL (Capital, Asset, Management, Earning and Liquidity) method is in a healthy predicate? Therefore, the goal to be achieved is to determine the financial performance of the Konawe Islands Sub-Branch Sultra Bank using the CAMEL method. This study uses quantitative and qualitative methods using a comparative approach, because the data used are in the form of numbers. The results showed that the financial performance of the Konawe Islands Sub-Branch of Southeast Sulawesi in terms of solvency (CAR) in 2019 was 5.21% healthy and in 2020 it was 38.62% unhealthy. In terms of the Quality of Earning Assets (KAP), it is healthy, namely 3.96% in 2019 and 4.09% in 2020. From a healthy Net Profit Margin (NPM), in 2019 it was 67.78% and in 2020 it was 63.08%. In terms of profitability (ROA) according to healthy BI standards, in 2019 it was 6.99% and in 2020 it was 5.03%. Meanwhile, in terms of liquidity and profitability, the Bank's financial performance is not healthy, both BOPO and LDR ratios. The BOPO ratio in 2019 was 185.61% and in 2020 it was 177.23%. The value of the LDR ratio in 2019 was 161.41% and in 2020 it was 139%, because it exceeded BI standards and was unable to utilize existing assets to obtain maximum profit and did not perform costs well.